The Influence of Career Development, Competence, and Work Performance on Employee Performance of Guarantee Company in Indonesia - Kurnia, Muhammad Alif; Rifa'i, Ahmad; Saptiani, Fenny (Integrasi Sains Media, 2025)
This study examines the impact of career development, competence, and work performance on employee performance at a state-owned credit guarantee company in Indonesia. Framed within the Ability-Motivation-Opportunity (AMO) theoretical model, the research seeks to contribute empirical insights into the dynamics of human resource effectiveness in state-affiliated financial institutions operating in emerging economies. Using an explanatory quantitative approach, data were collected through a structured questionnaire administered to all 35 Guarantee Company Indonesia employees. Statistical analysis was conducted using multiple linear regression via SPSS Version 27.0. The findings reveal that, when examined individually, career development and competence do not significantly affect employee performance. In contrast, work performance demonstrates a strong and statistically significant positive influence on performance outcomes. Notably, when analyzed collectively, the three variables—career development, competence, and work performance—exert a significant combined influence on employee performance. These results suggest that performance-based outcomes are the most critical factor influencing effectiveness, particularly in contexts where career planning and competency development may not be fully institutionalized. The study offers theoretical implications by reaffirming the centrality of performance motivation within the AMO model, while also providing practical guidance for human resource managers in optimizing employee contributions. It recommends strategic investments in performance recognition systems, targeted skills training, and integrated career frameworks to maximize organizational outcomes. Furthermore, the research highlights the importance of contextualizing HR strategies within the operational realities of Indonesia's guarantee service sector.